Kristy's big day - Martin, Ann M., 1955- (New York : Scholastic, 1987)
When her mother gets married, Kristy and the other members of the Baby-sitters Club have their hands full taking care of fourteen children at the wedding.
"An Apple paperback.".
4.7
3-6
Keywords: Babysitters -- Fiction; Weddings -- Fiction; Babysitters -- Fiction; Weddings -- Fiction